Integration of photovoltaic panels and green roofs: review and predictions of effects on electricity production and plant communities. Issue 1 (29th August 2016) - Schindler, Bracha Y.; Blank, Lior; Levy, Shay; Kadas, Gyongyver; Pearlmutter, David; Blaustein, Leon
Abstract : The integration of photovoltaic (PV) panels and green roofs has the potential to improve panel efficiency to produce electricity and enhance green roof species diversity and productivity. In this review, we provide an overview of research on the effects of green roofs on PV panel electricity production, and predict the expected effects of the PV panel on green roof plant communities. Previous studies suggest that PV panels are more efficient above a green roof than above several types of conventional roofs due to the cooling effect of green roofs on the temperature-sensitive PV cells. Some ecological studies on shade suggest that shade imposed by panels may enhance the biotic productivity of green roofs. Shade is often shown to be important for seedling survival, particularly in arid environments – so the effect of shade on plants may depend on climate and irrigation. Previous studies also suggest that shade variations over the roof area may enhance plant diversity, as such heterogeneity creates niches of light and moisture levels that are appropriate for a diversity of plants. These positive effects on plant diversity may lead to increased arthropod diversity as well. Additional replicated studies are needed to test the reciprocal effects of green roofs and PV, as past studies lacked replication. Future directions for research that could guide the design of green roof–PV integration include the effects of irrigation, plant diversity, and green area-to-panel ratio on the roof.